Slip role for unsteady MHD mixed convection of nanofluid over stretching sheet with thermal radiation and electric field - Daniel, Yahaya Shagaiya; Aziz, Zainal Abdul; Ismail, Zuhaila; Bahar, Arifah; Salah, Faisal (Indian journal of physics, 2020)
This paper mainly focuses on the impacts of slip conditions on the two-dimensional unsteady mixed convection flow of electrical magnetohydrodynamic nanofluid over a stretching sheet in the presence of thermal radiation, viscous dissipation, and chemical reaction. The synchronized impacts of electric and magnetic fields on the momentum and energy fields using Buongiorno nanofluid model were introduced to enhance thermal conductivity and hence create more pathways to heat transfer performance of nanofluid. The highly nonlinear couple systems of partial differential equations were modeled as a set of nonlinear ordinary differential equations by using suitably defined transformations which are then solved by implicit finite difference scheme known as Keller box method. It was established that velocity has a direct opposite relationship with electric and magnetic fields. The velocity, temperature, and concentration profiles caused intense decay to velocity slip, thermal slip, and solutal slip, with permeability condition. Magnetic field enhances the nanofluid temperature intensely with impermeable medium resulting in a decrease in heat transfer rate from the surface. The heat convection current is strengthened by viscous dissipation and radiative heat transfer prevailing impermeability, which leads to a reduction in heat transfer rate. Comparisons with previously published works seen in the literature were made, and the result was found to be in excellent agreement.